Socialization of Basic Artistic Gymnastics Movements for Elementary School Teachers - Herman Chaniago; Yafi Velyan Mahyudi; Wahyuningtyas Puspitorini; Desy Tya Maya Ningrum (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Physical education in elementary schools plays a strategic role in developing children’s fundamental movement skills, physical fitness, and character formation. However, the implementation of artistic gymnastics learning at the elementary level remains limited due to teachers’ lack of specific technical training, inadequate facilities, and the absence of structured instructional modules. This community service program aimed to enhance teachers’ competencies and improve students’ basic artistic gymnastics skills through a systematic and participatory approach. The program was conducted over one month and involved 15 physical education teachers and 120 students from five elementary schools. The activities included program socialization, a one-week intensive technical training for teachers using a learning-by-doing approach, and a three-week implementation phase for students. Evaluation was carried out through pre-test and post-test assessments of teachers’ knowledge and students’ gymnastics skills. The results showed a 27.2% increase in teachers’ knowledge scores and a 32.16% improvement in students’ basic gymnastics skills. These findings are consistent with experiential learning theory and previous studies indicating that practical-based teacher training significantly enhances pedagogical competence and positively impacts student learning outcomes. The program demonstrates that strengthening teacher capacity, applying progressive teaching methods, and ensuring safe learning environments are key factors in improving the quality of artistic gymnastics instruction in elementary schools.